Review paper: An overview and the time-optimal cruising trajectory planning - Somlo, Janos (Journal of Computer Science and Cybernetics, 2014)
In the practical application of robots, the part processing time has a key role. The part processing time is an idea borrowed  from manufacturing technology. Industrial robots usually are made to cover a very wide field of applications. So, their abilities, for example, in providing high speeds are outstanding. In most of the applications the very high speed applications are not used. The reasons are: technological (physical), organizational, etc., even psychological. Nevertheless, it is reasonable to know the robot's abilities. In this paper, a method which intends to provide the motion in every point of the path with possible maximum velocity is described. In fact, the path is divided to transient and cruising parts and the maximum velocities are required only for the latter.  The given motion is called ``Time-optimal cruising motion''. Using the parametric method of motion planning, the equations for determining the motions are given. Not only the translation motions of tool-center points, but also the orientation motions of tools are discussed. The time-optimal cruising motion planning is also possible for free paths (PTP motions). A general approach to this problem is proposed too.